2020
DOI: 10.1093/jtm/taaa054
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of SARS-CoV-2 infection in repatriation flights to Greece from three European countries

Abstract: Passengers on repatriation flights to Greece from the UK, Spain and Turkey were screened with oropharyngeal swabs on arrival for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Despite almost all passengers being asymptomatic, many tested positive (3.6% from the UK, 6.3% from Spain and 6.3% from Turkey), indicating widespread transmission of SARS-CoV-2 in these countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 3 publications
3
52
2
1
Order By: Relevance
“…Of these, two reported on the same study population, 16 46 so we linked the records and used data from the most detailed report. 16 Data from 31 empirical studies were collected in nine countries: China (21 studies, 1672people); 17 19 20 22 25-27 30 31 34-44 48 Japan (two studies, 116) people; 16 33 United States of America (two studies, 66 people); 18 23 and one study each from France (13 people), 21 Germany (two people), 47 Greece (39 people), 45 Malaysia (four people), 32 Thailand (11 people), 29 Vietnam (6 people). 24 One statistical modelling study that used data collected from all 634 tested passengers on a cruise ship, the Diamond Princess, 28 was considered separately from a study that reported on a subset of 104 of the passengers who were hospitalised in Japan.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, two reported on the same study population, 16 46 so we linked the records and used data from the most detailed report. 16 Data from 31 empirical studies were collected in nine countries: China (21 studies, 1672people); 17 19 20 22 25-27 30 31 34-44 48 Japan (two studies, 116) people; 16 33 United States of America (two studies, 66 people); 18 23 and one study each from France (13 people), 21 Germany (two people), 47 Greece (39 people), 45 Malaysia (four people), 32 Thailand (11 people), 29 Vietnam (6 people). 24 One statistical modelling study that used data collected from all 634 tested passengers on a cruise ship, the Diamond Princess, 28 was considered separately from a study that reported on a subset of 104 of the passengers who were hospitalised in Japan.…”
Section: Resultsmentioning
confidence: 99%
“…In the largest cohort in our set (6), researchers in Iceland used the following 2 methods to screen the general population for SARS-CoV-2 infection: an open invitation for interested parties to register online then provide biosamples at a Reykjavik location, and a text message sent to "randomly chosen Icelanders between the ages 20 and 70 years" inviting them to participate in the same manner as the first group (Table) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In all, 13 080 persons volunteered for the screening, 100 (0.8%) of whom tested positive for SARS-CoV-2.…”
Section: Cohorts Icelandmentioning
confidence: 99%
“…From 20 through 25 March 2020, a total of 783 Greek citizens were repatriated from Spain, Turkey, and the United Kingdom on 7 flights. Forty (5.1%) tested positive for SARS-CoV-2 (14). At the time of testing, 39 (97.5%) were asymptomatic.…”
Section: Greek Citizens Evacuated From Spain Turkey and The Unitedmentioning
confidence: 99%
“…The study of 565 Japanese citizens repatriated from China (26), found 13 positives: 4 asymptomatic and 9 symptomatic, based on screening on arrival. The other of 383 Greek citizens repatriated from UK, Spain, and Turkey (27) found 40 asymptomatic positives on arrival, 4 of whom later self-reported symptoms. Again, the likely initial exclusion of symptomatic people, and the lack of comprehensive follow up would both overestimate the asymptomatic rates.…”
Section: Rt-pcr = Reverse Transcription-polymerase Chain Reaction; Hcmentioning
confidence: 99%